Cultural orientation and social capital as predictors of condom use among internal migrants in China. (February 2016) - Du, Hongfei; Li, Xiaoming; Lin, Danhua; Tam, Cheuk Chi
Background: The global literature has revealed that cultural orientation, adaptation and social capital may influence HIV-related sexual behaviours among migrants. However, whether cultural orientations influence adaptation and social capital and thereby affect sexual behaviour is not well understood. Method: This study examined whether individualistic and collectivistic orientations, adaptation and social capital have direct and indirect effects on condom use among rural-to-urban migrants in China. We collected data from 641 migrants aged 17 to 30 years, in Beijing, China. Participants completed scales on individualistic orientation, collectivistic orientation, adaptation, social capital and condom use. Structural equation modelling was used for model testing. Results: Condom use was positively associated with an individualistic orientation and social capital. An individualistic orientation had an indirect effect on condom use via social capital. Women reported higher levels of condom use than men. Conclusion: Future sexual risk prevention and intervention programmes to improve sexual health should pay more attention to building social capital and engaging with relevant cultural factors.